2018
DOI: 10.24106/kefdergi.2448
|View full text |Cite
|
Sign up to set email alerts
|

Beden Eğitimi Öğretmenlerinin Mesleki Tükenmişlik Durumları ve Öğretim Sürecinde Bu Duruma Yol Açan Nedenler: Karma Araştırma Yaklaşımı

Abstract: Bu araştırmada beden eğitimi öğretmenlerinin mesleki tükenmişlik durumlarını karma araştırma yaklaşımı ile incelemek amaçlanmıştır. Araştırmanın çalışma grubunu, 2015-2016 Eğitim-Öğretim yılında Trabzon ve Ankara İllerindeki farklı eğitim kademelerinde görev yapan 242 beden eğitimi öğretmeni oluşturmuştur. Çalışmanın nicel verileri Maslach ve Jackson (1981) tarafından geliştirilen Türkçeye uyarlaması Ergin (1992) tarafından yapılan "Maslach Tükenmişlik Ölçeği", nitel veriler ise araştırmacılar tarafından hazır… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…In addition, in present study, the PE teachers claimed that the insufficient number of sports materials in their schools was another reason for their higher preference for the practice and command styles. This result related to sports materials represents one of the problems that are usually highlighted in studies conducted in Türkiye (Demirhan et al, 2008;Demirhan et al, 2014;Mirzeoğlu et al, 2019;Uğraş et al, 2019;Yılmaz et al, 2018). For example, Demirhan et al (2008) reported that large class sizes and limited materials may be some of the factors that cause teachers to prefer command and practice styles more in their lessons.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, in present study, the PE teachers claimed that the insufficient number of sports materials in their schools was another reason for their higher preference for the practice and command styles. This result related to sports materials represents one of the problems that are usually highlighted in studies conducted in Türkiye (Demirhan et al, 2008;Demirhan et al, 2014;Mirzeoğlu et al, 2019;Uğraş et al, 2019;Yılmaz et al, 2018). For example, Demirhan et al (2008) reported that large class sizes and limited materials may be some of the factors that cause teachers to prefer command and practice styles more in their lessons.…”
Section: Discussionmentioning
confidence: 96%
“…Ayrıca hem meslektaş ilişkilerinin yüksek düzeyde olduğunu belirten hem de meslektaşlar arasında sorunların yaşandığını ifade eden araştırmaların da olduğu alan yazında görülmektedir (Sağın, Güllü ve Uğraş, 2020;Yılmaz, Esentürk ve İlhan, 2018).…”
Section: Konu İle İlgili Yapılan Araştırmalarunclassified
“…In addition, it is seen in the literature that there are studies indicating that colleague relations are at a high level and that there are problems between colleagues (Sağın, Güllü and Uğraş, 2020;Yılmaz, Esentürk and İlhan, 2018).…”
Section: Research On the Subjectmentioning
confidence: 99%
“…Beden eğitimi dersinin akademik olarak etkisinin düşük olması, dersi geçmenin kolay olması ve beklentinin bu yönde olması, derse karşı ailelerin bilinçsiz olması, akademik kaygı içinde olmayan öğrenci ve velilerin dersi değersiz görmesi ve derse karşı olumsuz tutum içinde olmasını sağlamaktadır (Güven ve Önce, 2006;Oğul, 2010;Öncü ve Güven, 2011;Sezen, 2019;Sanz-Arazuri, Valdemoros, Ponce De Leon, Baena Exttremara,2018;Yılmaz, Esentürk ve İlhan, 2018).…”
Section: Aileler Ile Ilgili Sorunlarunclassified